Frequency of early initiation of breastfeeding among women in Thatta, Sindh and factors associated with it: A secondary data analysis - Barkat, Rahil; Jiwani, Ahsun; Rahim, Anum; Sherwali Khan (Journal of the Pakistan Medical Association, 2022)
Introduction: It is recommended by the World Health Organization to initiate breastfeeding within first hour of birth. In recent time, many efforts are being taken by international and national stakeholders to promote mothers to initiate early breastfeeding. However, only 42% of newborns in South Asia and 45% of newborns in world are put to breastfeeding within first hour of birth. The aim of this study was to determine the prevalence of early initiation of breastfeeding and factors associated with it in rural areas of Sindh, Pakistan. Methodology: The data for this study were extracted from the survey related to Exclusive breastfeeding among women in Thatta, 2019. Survey was implemented in areas of Thatta registered in Maternal and Neonatal Health Registry (MNHR). MNHR is a population-based study for low- and middle-income countries (LMICs) to assess pregnancy related outcomes. About 397 women with complete information on timing of initiation of breastfeeding were used in the analysis. Results: The early initiation of breastfeeding to their newborn baby i.e. within first hour of the birth, were found in 20.4% of mothers. Factors associated with early initiation of breastfeeding include adequate knowledge (AOR=3.63, 95% CI= 1.99-6.59), place of delivery AOR=2.66 (95% CI=1.51-4.67), gestational age of baby (AOR= 1.89, 95% CI=1.10-3.24) and Age of mother (AOR=1.07, 95% CI=1.02-1.13). Conclusion: Providing counselling and health education for mother before, during and after the pregnancy are important to motivate mothers to initiate breastfeeding early and continue exclusive breastfeeding for recommended period i.e. 6 months.